Harvest growth stages in soybean cultivars intended for silage - Oliveira, Raquel Dias (2016)
This study aimed to characterize the harvest phenological stages of soybean cultivars intended for silage. Cultivars were evaluated for dry weight of the composite sample, branches, leaves and pods; wet mass of branches, leaves, pods and ground natural matter. This experiment was a 3 x 2 factorial randomized block design, with four replications each, where the first factor corresponds to the harvest stage: R4, R5 and R6; and the second factor refers to two soybean maturity groups (8.0 and 8.1). A significant interaction was detected only for ground natural matter. Higher values of most traits evaluated were observed for the R6 harvest phenological stage. The cultivar with maturity group 8.0 showed higher values for ground natural matter.